Multi‐transgenic pigs for xenoislet transplantation. (5th February 2013) - Ayares, David; Phelps, Carol; Vaught, Todd; Ball, Suyapa; Monahan, Jeff; Walters, Anneke; Giraldo, Angelica; Bertera, Suzanne; van der Windt, Dirk; Wijkstrom, Martin; Cooper, David K. C.; Bottino, Rita; et al.
<x xml:space="preserve">Abstract</x> Background: Islets obtained from genetically‐engineered (GE) pigs with Gal‐knockout (GTKO) and high expression of hCD46 have shown long‐term function and successful correction of insulin independence in nonhuman primates (NHP). Two anti‐coagulant genes (hTFPI and hCD39), and an immunosuppressive gene (pCTLA4Ig) have been added to the GTKO/hCD46 background, using an islet‐specific expression system, for inhibition of thrombosis, inflammation, early islet loss, and rejection. Transplant outcomes are being tested in a diabetic monkey model using adult islets from these multi‐transgenic pigs. Methods: Three individual vectors (CD39ins, TFPIins and CTLA4Igins), each under control of the rat insulin II promoter and mouse PDX‐1 enhancer, were transfected alone or in combination into GTKO/hCD46 pig fibroblast cells. GTKO/hCD46/CD39ins, GTKO/hCD46/TFPIins/CTLA4Igins, and GTKO/hCD46/CD39ins/TFPIins/CTLA4Igins cell lines were used for nuclear transfer (NT) to produce pregnancies. Cloned pigs were analyzed for transgene expression in pancreas, heart, and liver by IHC, Western, and real‐time PCR. Glucose metabolism in the various GE pigs was determined by measurement of blood glucose, c‐peptide, and via intravenous glucose tolerance tests (ivGTT) or arginine stimulation test. GE islets from adult pigs were transplanted intraportally into STZ‐diabetic monkeys using an ATG/MMF/anti‐CD154 immunosuppression regimen. Results: Viable multi‐transgenic pigs with three, four, or five different genetic modifications were produced. Three different pig lines were established: (i) GTKO/hCD46/CD39ins, (ii) GTKO/hCD46/TFPIins/CTLA4Igins, and (iii) GTKO/hCD46/CD39ins/TFPIins/CTLA4Igins. IHC revealed robust islet‐specific expression of CD39, TFPI and CTLA4Ig in pancreas, with only background expression in heart and liver. Western analysis showed strong pCTLA4Ig expression only in the pancreas. Blood glucose metabolism was normal in all GE pigs tested. Islets from GE pigs containing the TFPI transgene, when mixed with human blood, showed prolonged clotting times. Early islet loss (IBMIR) was reduced 5–7 fold in NHP transplants using islets from 4‐GE and 5‐GE pigs vs. 2‐GE pig islets. Conclusions: (i) Healthy multi‐transgenic pigs with islet‐specific expression of hCD39, hTFPI, and pCTLA4Ig were produced. (ii) Glucose metabolism was normal in these GE pigs. (iii) GE islets showed anti‐coagulation activity in vitro, and protection from IBMIR in vivo in NHP transplants. (iv) GE islets transplanted into diabetic monkeys demonstrated prolonged survival, function, and complete normalization of blood glucose levels for up to 1 year.